2020
DOI: 10.56093/ijans.v90i3.102414
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dry period therapy on prevalence of mastitis in buffaloes in Haryana

Abstract: The study attempts to compute the effect of dry period therapy on occurrence of mastitis in buffaloes with the help of control (164 buffaloes) and treatment (330 buffaloes) groups at different stages as per disease diagnostic protocol. The data pertains to the year 2018-19. The study concludes overall prevalence of SCM at dry-off was 83.81% and at 5 days postpartum was 38.87% at animal level. In treatment group, prevalence of SCM was 89.70% and 28.48% at dry-off and 5 days postpartum respectively whereas 73.17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…96 The 13 C NMR spectral data of the H 3 L ligand displayed distinctive signals for the -HC=N-and Ar-C-O groups, occurring at δ 165.74 ppm and δ 160.88 ppm, respectively. 97 Following complexation with Zn metal, these signals appeared a shift toward the deshielded region at δ 171.15 ppm and 167.26 ppm, respectively. This shift suggested that the lone pair electron density of nitrogen and oxygen atoms was directed toward the Zn atom, indicating the formation of the Zn (II) complex.…”
Section: H Andmentioning
confidence: 99%
“…96 The 13 C NMR spectral data of the H 3 L ligand displayed distinctive signals for the -HC=N-and Ar-C-O groups, occurring at δ 165.74 ppm and δ 160.88 ppm, respectively. 97 Following complexation with Zn metal, these signals appeared a shift toward the deshielded region at δ 171.15 ppm and 167.26 ppm, respectively. This shift suggested that the lone pair electron density of nitrogen and oxygen atoms was directed toward the Zn atom, indicating the formation of the Zn (II) complex.…”
Section: H Andmentioning
confidence: 99%
“…They also reported that the treated animals clinically improved significantly and remain longer in herd as compared to control cows. Boora et al (2020) studied effect caused by aDAT in SCM and IMI in 330 buffaloes and concluded that overall, 63.02 percent buffaloes suffering from IMI were totally cured in the dry-off period and cured 3.85 times greater as compared to those which did not receive the treatment.…”
Section: Table 4: Bacteriological Cure Rate Of Treatment Groups At Da...mentioning
confidence: 99%
“…Schiff bases and their metal complexes are extensively utilized in numerous applications, such as chemosensors, 5,6 catalysis, 7,8 and intermediates in organic synthesis, 9,10 dye and pigments, 11 and others 12 . In the past decades, people have paid great attention to the research progress of Schiff‐base metal complexes due to their biological activities involving antibacterial, 13–16 antiproliferative, 17 antiapoptotic, 18,19 antimalarial and anti‐inflammatory activities 20–22 and as urease inhibitors. Schiff bases show a variety of biological activities, which may involve many reasons, but their structure containing azomethine or imine group is probably one of the reasons for their important role 23 .…”
Section: Introductionmentioning
confidence: 99%